The Abilities of English and Asean Economic Community; The Challenges for Islamic High School Students - Abrar (STIS DAFA MATARAM, 2018)
The ASEAN Economic Community is a term that we often hear lately. This term often appears in various types of media both print and electronic. The term is certainly very synonymous with the term that was first born as the European Economic Community (EEC). This journal explores how the ability of English students specifically in Islamic higher education will be a challenge in facing the Asean Economic Community. The method used is a qualitative method by interviewing representatives of 5 students and 1 English lecturer in 5 private Islamic colleges on Lombok island. Based on the results of interview on December 2018, they are: a. English has not become a priority in the development of universities, b. Student ability is still weak in English, c. MEA is not considered a big challenge in economic development.